EDUCATIONAL MARKETING STRATEGIES ON THE MARKET OF HIGHER EDUCATION SERVICES - Andreea, Neacsu Nicoleta; Paula, Armasar Ioana (PEOPLE: International Journal of Social Sciences, 2019)
The present article mainly aims at identifying the core aspects which have influenced the Romanian and foreign students’ decision to apply for mobility and the impact the mobility opportunities have had on the promotion of the universities they belong to, as a marketing technique. In this respect, the authors have conducted a qualitative exploratory empirical research study. As part of it, students from several university centres have been interviewed, the findings allowing the authors to establish the extent to which the respondents appreciate the types of mobility the universities offer at present, the extent to which they succeed in meeting their expectations and the way mobility programmes are promoted by universities. The research is based on the semi-structured in-depth interview. Based on the findings, the authors recommend the management of the Romanian universities should develop strategies to promote educational mobility which should offer more information and which should succeed in better communicating the advantages to students.